Coping with breast cancer: The roles of clergy and faith - Johnson, Sarah C. (Journal of religion and health, 1991)
This paper describes the experiences of 103 breast cancer patients with home pastors and hospital chaplains. Attention was directed at the activities of clergy, the degree to which religious and nonreligious interactions were satisfying to the women, and how these related to their personal faith orientation. Because of the issues of sexual identity and attractiveness entailed by breast cancer, the role of female clergy was also explored. It is evident that religion is an extremely important resource for the majority of these breast cancer patients, and an intrinsic religious orientation helps one cope with breast cancer.